2013
DOI: 10.17795/ijep9320
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Birds Surveillance for Newcastle Disease Virus (NDV) in Khozestan Province

Abstract: Background:Wild aquatic birds are considered as reservoir hosts for Newcastle disease viruses (NDVs) and may act as vectors for transferring these viruses to poultry, causing outbreaks of disease. Recent studies suggested that the velogenic viruses arise from avirulent strains originating from wild birds. Objectives: The primary objective of this study was to determine whether the aquatic birds of Khozestan province were infected with NDV. Materials and Methods: In winter, 24 Muscovey ducks from Shoshtar, 20 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…Regarding the method of detection and differentiation of NDV used in this study, it has been documented that although RT‐PCR and RRT‐PCR cannot replace the virus isolation completely, they are recommended for surveillance programs technique and are useful for rapid screening of at‐risk poultry flocks (Abd‐Elfatah et al., 2021; Camenisch et al., 2008; Wise et al., 2004). The positive cases of waterfowl to Newcastle virus as observed in this study (Table 5) are much higher than previously reported from exotic zoo birds in Tehran (Madadgar et al., 2013) but less than that reported from aquatic birds in Khuzestan province (Talazade & Mayahi, 2013). Comparison of the results obtained in this study with those reported from the neighbouring countries indicated that the number of positive cases in our study was also higher than those reported from Azerbaijan (Zeynalova et al., 2015), Turkey (Boynukara et al., 2013; Turan et al., 2020) and Pakistan (Wajid et al., 2017; Wajid et al., 2018) but less than that reported from Oman (Al‐Shekaili et al., 2015).…”
Section: Discussioncontrasting
confidence: 65%
“…Regarding the method of detection and differentiation of NDV used in this study, it has been documented that although RT‐PCR and RRT‐PCR cannot replace the virus isolation completely, they are recommended for surveillance programs technique and are useful for rapid screening of at‐risk poultry flocks (Abd‐Elfatah et al., 2021; Camenisch et al., 2008; Wise et al., 2004). The positive cases of waterfowl to Newcastle virus as observed in this study (Table 5) are much higher than previously reported from exotic zoo birds in Tehran (Madadgar et al., 2013) but less than that reported from aquatic birds in Khuzestan province (Talazade & Mayahi, 2013). Comparison of the results obtained in this study with those reported from the neighbouring countries indicated that the number of positive cases in our study was also higher than those reported from Azerbaijan (Zeynalova et al., 2015), Turkey (Boynukara et al., 2013; Turan et al., 2020) and Pakistan (Wajid et al., 2017; Wajid et al., 2018) but less than that reported from Oman (Al‐Shekaili et al., 2015).…”
Section: Discussioncontrasting
confidence: 65%
“…This virus can cause diarrhea, respiratory problems, circulatory and central nervous system disorder. 7…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we propose that urban feral birds possess better resistance against the country's endemic pathogens, such as the velogenic strain of avian orthoavulavirus-1 (AOAV-1) which causes clinical Newcastle disease (ND) in wild birds and poultry (commercial and backyard). Wild/feral birds, including waterfowl, shorebirds, doves, pigeons, double-crested cormorants, and other free-flying birds serve as continuous reservoirs of AOAV-1 and shed the virus into the environment without displaying typical clinical signs [9][10][11] . However, there is a paucity of experimental evidence on the spectra of immunocompetence among feral birds representing either urban or rural settings.…”
Section: Introductionmentioning
confidence: 99%